2023
DOI: 10.3389/fcvm.2022.1072191
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute aerobic exercise on arterial stiffness in individuals with different body fat percentages: A cross-sectional study

Abstract: BackgroundBody fat percentage were positively correlated with arterial stiffness, but the acute change in arterial stiffness after aerobic exercise in individuals with different body fat percentages remains unclear. This study was aimed to determine the effect of acute aerobic exercise on arterial stiffness in individuals with different body fat percentages.MethodsIndividuals who both participated in the seventh survey of the Kailuan study and the fifth iteration of National Physical Fitness Monitoring were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In a Chinese study involving 940 male participants (average age 36.8 years, average BMI 26 kg/m 2 ) who underwent a two-stage load test on cycle ergometry, the results indicated that at the end of the exercise, HR increased in all quintiles of body fat percentage, while BP did not show a significant increase [49].…”
Section: Discussionmentioning
confidence: 99%
“…In a Chinese study involving 940 male participants (average age 36.8 years, average BMI 26 kg/m 2 ) who underwent a two-stage load test on cycle ergometry, the results indicated that at the end of the exercise, HR increased in all quintiles of body fat percentage, while BP did not show a significant increase [49].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that PA negatively associated with the prevalence of MetS [25,26]. Recent studies have shown that PA or aerobic exercise can improve various components of MetS, including body composition [27,28], insulin resistance and lipid metabolism [29][30][31], and cardiovascular function [31,32]. Specifically aerobic exercise reduces chronic inflammation, increases energy expenditure, and increases expression of PGC-1a, which protects against mitochondrial diseases such as apoptosis and oxidative damage [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%